Diagnostic Pitfalls in Papillary Muscle Rupture-Associated Acute Mitral Regurgitation after Acute Myocardial Infarction - Akiko Kameyama; Hiroshi Imamura; Hiroshi Kamijo; Kanako Takeshige; Katsunori Mochizuki; Kenichi Nitta (Case Reports in Critical Care)
Papillary muscle rupture (PMR) is a rare and fatal complication of acute myocardial infarction (AMI). We report a case of acute mitral regurgitation (MR) due to PMR with pulmonary edema and cardiogenic shock following AMI with small myocardial necrosis. An 88-year-old woman was brought to our emergency department in acute respiratory distress, shock, and coma. She had no systolic murmur, and transthoracic echocardiography was inconclusive. Coronary angiography showed obstruction of the posterior descending branch of the right coronary artery. Although the infarction was small, the hemodynamics did not improve. Transesophageal echocardiography established papillary muscle rupture with severe mitral regurgitation 5 days after admission. Thereafter, the patient and her family did not consent to heart surgery, and she eventually died of progressive heart failure. Physicians should be aware of papillary muscle rupture with acute mitral regurgitation following AMI in patients with unstable hemodynamics, no systolic murmur, and no abnormalities revealed on transthoracic echocardiography.